The effect of vitamin D supplementation on the frequency and course of recurrent respiratory diseases in children - Yu.V. Marushko; S.I. Yesipova; T.V. Hyshchak (Zaslavsky O.Yu., 2023)
Background. Recurrent and prolonged course of respiratory infections leads to the formation of chronic foci of inflammation, the persistence of viruses, impaired physical and psychomotor development, and a decrease in the child's immunity. Given the participation of vitamin D (VD) in the regulation of the body's immune response, the study of its role in the development and course of recurrent respiratory diseases in children remains relevant. The purpose is to study the effect of vitamin D supplementation on the frequency and course of recurrent respiratory diseases in children. Materials and methods. We examined 52 children with recurrent respiratory infections aged 4 to 10 years. Children were examined before and after VD supplementation according to the study criteria: the average frequency of acute respiratory infection (ARI) episodes per year, the severity of the clinical manifestations of ARI episode, its average duration, the frequency of antibiotic prescriptions and outpatient visits to the doctor. Results. It was found that at the beginning of the examination, the level of 25(OH)D in the blood serum ranged from 11.1 to 29.9 ng/ml, 22 (42.3 %) children had VD deficiency. An analysis of the frequency of ARI episodes per year showed that children with VD deficiency were ill more often than children with a sufficient level of VD (p < 0.001). According to the results of the study, it was found that VD supplementation contributes to a decrease in the frequency of ARI episodes from 8.7 ± 1.7 to 6.8 ± 1.2 times a year (p < 0.001), a decrease in the average number of symptoms of an episode of acute respiratory infections per year from 5.5 ± 0.5 to 4.5 ± 0.5 and their manifestations from 9.2 to 7.41 points (p < 0.001), a decrease in the duration of ARI episode from 6.0 ± 1.7 to 5.7 ± 1.5 days (p = 0.003), as well as a decrease in the number of outpatient visits from 5 to 4 (p = 0.004) and antibiotic prescriptions from 61 to 38 (p < 0.001). Conclusions. VD supplementation improves the course of respiratory diseases in children. The study was carried out in accordance with the Declaration of Helsinki principles. The study protocol was adopted by the ethics committee of the institution indicated in the work. The informed consent of the children's parents was obtained.